Analytical Study Of Total Performance Time and 50m Legs Performance Time In All Types of Swimming Strokes For Advance Swimmers - Thamr, Ahmed; Qusay, Waled (Journal of Physical Education, 2016)
The importance of the research lies in studying swimmers' times and work duringleg movement in the four swimming strokes through identifying its different effect inperformance from one type to another. The problem of the research lies in the lack ofdevelopment in swimming achievement compared to Arabic and world records. Theresearchers used the descriptive method and the subject was (8) swimmers. The researcherperformed two experiments; the first one 50m total performance time and the second 5m legsperformance time. The research showed the great effect of legs' movement. Finally theresearchers recommended paying attention to legs' movement due to their great effect onperformance as well as making similar researches to develop Iraqi records.